The power of moral authority - Andrukaitienė, Irena (Genocidas ir rezistencija, 2021)
Every era has its own spiritual leaders. One of the moral authorities of the nation in the second half of the 20th century was His Eminence Cardinal Vincentas Sladkevičius. His blessing supported the Church’s resistance to the restrictions on freedom of conscience during the Soviet years, the underground Chronicle of the Catholic Church in Lithuania, the outbreak of the Sąjūdis reform movement, and the restoration of independence – the adoption of the Act of March 11.
Keywords: Catholic Church; soviet Lithuania; repression; Vincentras Sladkevičius